2022
DOI: 10.1007/s11104-022-05819-1
|View full text |Cite
|
Sign up to set email alerts
|

Roles of salicylic acid in selenium-enhanced salt tolerance in tomato plants

Abstract: AimsSelenium (Se) has been reported to mitigate the harmful effect of salt stress on plants, however the internal mechanisms are still unknown. Here, the effects of Se supplementation on tomato under salt stress were investigated. MethodsThe biomass, relative electrical conductivity (REC), relative water content (RWC), malondialdehyde (MDA), soluble sugar and proline content, and the regulation of plant hormones of Se application in tomato were investigated after exposure to Se and salt stress treatments. Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 74 publications
0
13
0
Order By: Relevance
“…According to 46 , soluble sugars do not merely function as the basic components of cells and a source of metabolic energy, but they also operate as signals that modulate several mechanisms associated with plant growth and development. Furthermore, it has been suggested that soluble sugars may act as a chelating agent, causing Na + to be trapped within starch granules contributing to eliminating Na + toxicity in salt-stressed plants 47 . On the other hand, the reported decrease in soluble proteins and free amino acids after salinity stress in our investigation is consistent with the reports of 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…According to 46 , soluble sugars do not merely function as the basic components of cells and a source of metabolic energy, but they also operate as signals that modulate several mechanisms associated with plant growth and development. Furthermore, it has been suggested that soluble sugars may act as a chelating agent, causing Na + to be trapped within starch granules contributing to eliminating Na + toxicity in salt-stressed plants 47 . On the other hand, the reported decrease in soluble proteins and free amino acids after salinity stress in our investigation is consistent with the reports of 48 , 49 .…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it has been widely recognized as a critical indicator in most physiological research. Salinity decreases turgor pressure and DNA synthesis by inducing osmotic stress, ion imbalance, and ion toxicity [ 45 ]. All salinity-induced changes in plant metabolism, which include physiological and biochemical processes such as photosynthesis, ion homeostasis, and antioxidant activity, lead to reduced growth [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in bean ( Phaseolus vulgaris L.), Se biofortification resulted in enhanced shoot and root fresh weight, chlorophyll, carotenoid, RWC, proline, total soluble sugars, peroxidase, and catalase enzymes when plants were exposed to a concentration of 50 mM NaCl [ 44 ]. Additionally, foliar Se application improved photosynthesis and water use efficiency (WUE) in tomato plants under salinity stress conditions, leading to increased tomato plant growth and a reduction in oxidative stress-induced damage [ 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the deleterious effects of salt stress on RWC and EL, foliar application of salicylic acid in concentrations between 1.0 and 1.2 mM mitigated the effects of irrigation water salinity in the first cropping cycle of sour passion fruit. Salicylic acid acts to protect plant cells from the toxicity caused by ion accumulation and improves antioxidant activity, nitrogen metabolism, and water absorption in plants [ 46 , 47 ], increasing leaf turgor and reducing cell membrane damage [ 1 ].…”
Section: Discussionmentioning
confidence: 99%